2021
DOI: 10.1002/est2.268
|View full text |Cite
|
Sign up to set email alerts
|

New shape‐stabilized phase change materials obtained by single‐screw extruder

Abstract: Shape‐stabilized phase change materials (SS‐PCM) are promising materials given their potential to control leakage of liquid PCM. However, SS‐PCM still has low thermal conductivity and high flammability, which are important properties for several applications, such as the thermal indoor comfort in buildings. In this study, two new polymeric SS‐PCM were developed and their properties were optimized by the use of different additives. Both high‐density polyethylene (HDPE) and polyoxymethylene (POM) work as matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Salgado‐Pizarro et al. found that shape‐stabilising PCMs with HDPE and Polyoxymethylene (POM) whilst adding carbon graphite and magnesium hydroxide through extrusion can obtain a chemically stable PCM with several potential applications, e. g. thermal indoor comfort in buildings [126] . However, researchers need to conduct more studies regarding how the extrusion parameters affect the TES performance.…”
Section: Energy‐saving Buildings With Pe‐pcmsmentioning
confidence: 99%
“…Salgado‐Pizarro et al. found that shape‐stabilising PCMs with HDPE and Polyoxymethylene (POM) whilst adding carbon graphite and magnesium hydroxide through extrusion can obtain a chemically stable PCM with several potential applications, e. g. thermal indoor comfort in buildings [126] . However, researchers need to conduct more studies regarding how the extrusion parameters affect the TES performance.…”
Section: Energy‐saving Buildings With Pe‐pcmsmentioning
confidence: 99%
“…8 Solid-to-liquid PCMs (or vice versa) are the most common materials used to store energy due to their ease of contain. 9 PCMs have high phase change enthalpy, 10 controllable volume shape, 11 and so, solid-liquid (or vice-versa) PCMs are the most appropriate heat storage materials option. 12 At heating (charging phase), PCM melts when its temperature rises to reach the degree of melting, it absorbs its latent heat of melting at that temperature, and continues absorbing heat until it melts completely to the liquid phase, the same process is reversed with heat rejection during (discharging phase) that includes solidification process till the liquid PCM changes to a solid state after the rejection of all latent heat of solidification.…”
Section: Introductionmentioning
confidence: 99%